JUMPA Vol.3 No.3 Okt 2016 HUBUNGAN MOTIVASI KERJA DENGAN KINERJA KARYAWAN DI FAVEHOTEL GATOT SUBROTO JAKARTA: HUBUNGAN MOTIVASI KERJA DENGAN KINERJA KARYAWAN DI FAVEHOTEL GATOT SUBROTO JAKARTA - Muhammad Iffandi Universitas Sahid, Jakarta; Titin Astuti Universitas Sahid, Jakarta; Kania Ratnasari Universitas Sahid, Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2016)
One of the important assets owned by the company cannot be separated from the employee’s performance. To obtain a good performance, it is required an employee high motivation. Certainly, a good leader will always motivate the employees with the goal of keeping the spirit of the work and provide maximum performance. Motivation is an important factor to obtain a good performance. This research was conducted in order to determine the relationship work motivation and performance of employees at favehotel Jakarta. The method used in this research is descriptive quantitative method by using SPSS to help analyze the data obtained from the field. Data in this study were obtained by distributing questionnaires to 40 respondents as the population, then processed using the correlation formula of Rank Spearman, to determine whether there is a relationship between work motivation and employee performance, continues to find the correlation coefficient (R) to determine the relationship posed motivation work on employee performance. The results showed that the work motivation had a strong relationship with employee performance. It was evident from the results of the calculation of correlation coefficient of 0.623. This suggests a positive relationship between work motivation and employee performance with coefficient of determination obtained further by 38.8% and the remaining 61.2% is influenced by other factors.